Analisis Upaya Guru dalam Membentuk Sikap Disiplin Siswa Kelas III di UPTD SDN Tanjung Jati 2 Bangkalan - Diah Lailatur Rohmah; Nilamsari Damayanti Fajrin (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This study aims to analyze teachers' efforts in forming disciplined attitudes in grade III students of SDN Tanjung Jati 2. The main focus of this research is on the efforts teachers use to instill discipline and the factors that support and hinder this process The approach used in this study is qualitative, with data collection through interviews, observations, and documentation aimed at grade III teachers. The results of the study revealed that: 1) Teachers' efforts in forming students' disciplined attitudes include habituation, role models, application of punishment, giving rewards, and consistency in implementing rules. 2) Factors that support teachers' efforts in forming students' disciplined attitudes include the active role of the principal, cooperation between teachers, and parental involvement. 3) Conversely, factors that hinder the formation of students' disciplined attitudes include the influence of social interactions between students and the less supportive attitudes of parents.